2013
DOI: 10.1016/j.neuroscience.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Threat bias in mice with inactivating mutations of Prkar1a

Abstract: Anxiety disorders are associated with abnormalities in the neural processing of threat-related stimuli. However, the neurobiological mechanisms underlying threat bias in anxiety are not well understood. We recently reported that a Prkar1a heterozygote (Prkar1a+/-) mouse with haploinsufficiency for the main regulatory subunit (R1α) of protein kinase A (PKA) exhibits an anxiety-like phenotype associated with increased cAMP signaling in the amygdala. Prkar1a+/- mice provide a novel model to test the direct effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…All behavioral testing was performed, as previously reported [31-33], between the hours of 1300-1700 h. One behavioral test per day was performed, with a span of at least two days between tests. The order of behavioral tests was randomly assigned [27]. Two scorers performed behavioral testing and obtained scoring of all results in a blinded fashion (without knowledge of the genotypes of the mice under observation).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All behavioral testing was performed, as previously reported [31-33], between the hours of 1300-1700 h. One behavioral test per day was performed, with a span of at least two days between tests. The order of behavioral tests was randomly assigned [27]. Two scorers performed behavioral testing and obtained scoring of all results in a blinded fashion (without knowledge of the genotypes of the mice under observation).…”
Section: Methodsmentioning
confidence: 99%
“…Elevated plus maze (EPM) testing was performed as described previously [24, 27, 32, 33]. Mice were transported in their home cages to the testing room two hours prior to acclimate prior to testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research with a mouse model with the loss of one Prkar1a allele showed augmentation of anxiety-like behaviors associated with an increase in PKA activity in the BLA and CEA and an increase in threat bias [115,116]. Functionally, loss of Prkar1a is associated with excess PKA signaling, and these findings highlight the importance of cAMP/PKA signaling in neural areas relevant to the emotional processing of threat (i.e.…”
Section: Direct/indirect Inhibition Of the Pka Pathway: Lessons From mentioning
confidence: 75%